Designing the ArthaWira Platform as a Solution for Digital Transformation and Strengthening the Competitiveness of SMEs in Indonesia - Vina Nur Vina Febrianti; S.Azzahra Puja Sukma Permana; Sopia Rahayu; Syifa Nur Latifah; Maryam Siti Azizah (Universitas Dehasen Bengkulu, 2026)
ASMEs are one of the sectors that play an important role in Indonesia's economy because they can create jobs, improve people's welfare, and support national economic growth. However, many SMEs still face various problems, such as limited digital skills, difficulty in obtaining capital, lack of managerial skills, and limited market conditions. This study aims to design the Arthawira platform as a digital solution that can support the digital transformation and improve the competitiveness of SMEs in Indonesia. The method used in this study is a descriptive qualitative approach by conducting interviews and literature studies on three SMEs in food trade, culinary, and crafts. The study reveals that the ArthaWira Platform is designed as an integrated digital ecosystem, offering features for business management, financial record-keeping, digital marketing, access to financing, as well as educational services.and support for MSMEs. The implementation of this platform is backed by a collaborative strategy involving the government, financial institutions, academics, and the private sector to ensure the program's sustainability. ArthaWira Platform is expected to boost digital capabilities, operational efficiency, market access, and the competitiveness of MSMEs in the digital economy context. In other words, this platform has the potential to be an innovative solution to accelerate inclusive and sustainable MSME growth in Indonesia